The Effects of the Pancasila Student Profile Strengthening Project on the Mutual Cooperative Attitude of Students at SMP Negeri 8 Purwokerto - Ega Lestari; Eko Priyanto; Elly Hasan Sadeli (UM Purwokerto Press, 2024)
This study aims to determine the effects of the Pancasila Student Profile Strengthening Project on the mutual cooperative attitude of students at SMP Negeri 8 Purwokerto. The research method used in this study is descriptive analysis with a quantitative approach. The population in this study consists of seventh and eighth-grade students at SMP Negeri 8 Purwokerto. The sample size is 237 students, determined using a simple random sampling technique. Data collection techniques employed in this study include questionnaires, observations, interviews, and documentation. The research findings indicate a positive and significant impact of the Pancasila Student Profile Strengthening Project on the mutual cooperative attitude of students at SMP Negeri 8 Purwokerto. The influence of the Pancasila Student Profile Strengthening Project on students' mutual cooperative attitudes is measured at 0.376, which can be interpreted as the independent variable (X) - the Pancasila Student Profile Strengthening Project - contributing 37.6% to the dependent variable (Y) mutual cooperative attitude. This can be seen in the students' mindset, which fosters collaboration and teamwork, social sensitivity and concern, and a sharing attitude.